Optimization of ultraviolet pasteurization conditions of shalgam (şalgam) juice and determination of its shelf life - Doğan, Kübra (My University, 2017)
In recent years, production of fermented and probiotic vegetable juices has gained importance in around the world with the increasing demand of consumers for healthier foods. Several preservatives are used and heat treatment is performed to commercial shalgam juice after fermentation in order to increase its shelf life. The purpose of this study was to investigate the effect of continuous system ultraviolet (UV) treatment as an alternative non-thermal food preservation method on quality characteristics of shalgam juice with the aim of eliminating the disadvantages of thermal treatment and preservative use in shalgam juice. For this aim, fermented shalgam juice samples were treated to 5 UV processing conditions comprising from 3 different flow rates (1500-2500-3500 ml / min), 2 different temperatures (5-25 ˚C) and 2 different UV intensities (5.1-10.1 mW / cm2). Then the samples were analyzed for their microbiological, physicochemical, bioactive and sensorial characteristics during storage for 5 months at 4 °C. In the results, UV treatment gave comparable and favorable results in terms of microbiological and bioactive properties of the shalgam juices with heat treatment while UV treated samples got higher (P<0.05) sensorial scores than the heat treated one. About 3 logs higher ii inactivation in TMAB counts were observed in UV treated samples than the control. In conclusion, UV treatment exhibited better product quality properties and was approved as an alternative non-thermal preservation method instead of conventional heat treatment process to be used in shalgam juice production.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2017
Keywords: Ultraviolet (UV); Fermentation; Shalgam; Shelf life; Non-thermal food preservation methods